International encyclopedia of the social & behavioral sciences - Wright, James D. (Elsevier, 2015)
Fully revised and updated, the second edition of the International Encyclopedia of the Social and Behavioral Sciences, first published in 2001, offers a source of social and behavioral sciences reference material that is broader and deeper than any other. Available in both print and online editions, it comprises over 3,900 articles, commissioned by 71 Section Editors, and includes 90,000 bibliographic references as well as comprehensive name and subject indexes. Provides authoritative, foundational, interdisciplinary knowledge across the wide range of behavioral and social sciences fields.